2016
DOI: 10.3390/atmos7090113
|View full text |Cite
|
Sign up to set email alerts
|

Possible Impact of Climate Change on the Quality of Apples from the Major Producing Areas of China

Abstract: Meteorological conditions are important environmental factors affecting apple quality. To understand the possible impact of climate change on the apple quality of the major producing areas in China and assess the quality of major apple species (e.g., Fuji, Ralls, and Golden Delicious), we studied the variation trends and abrupt change characteristics of six major climate factors affecting seven physicochemical indices of apple quality across five apple regions, including the Loess Plateau, Bohai Bay, the Old C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…The analysis of variance showed that there were statistically significant difference (p < 0.01) between growing seasons (Table 7), thus indicating that weather conditions mainly the average air temperature determines the content of TA in apples. The same statement was presented earlier, showing that the average summer temperature strongly correlated with the content of TSS and TA (Qu, Zhou, 2016). After three months of storage, a significant decline in acidity was observed for all storage technologies tested, except for ULO2 (the 2 nd harvest).…”
Section: Resultssupporting
confidence: 87%
“…The analysis of variance showed that there were statistically significant difference (p < 0.01) between growing seasons (Table 7), thus indicating that weather conditions mainly the average air temperature determines the content of TA in apples. The same statement was presented earlier, showing that the average summer temperature strongly correlated with the content of TSS and TA (Qu, Zhou, 2016). After three months of storage, a significant decline in acidity was observed for all storage technologies tested, except for ULO2 (the 2 nd harvest).…”
Section: Resultssupporting
confidence: 87%
“…Size and quality of apples are also influenced by summer temperatures and light conditions. Several authors have highlighted and reviewed the effect of average summer temperatures on internal quality attributes, e.g., titratable acid content, anthocyanin content in the peel, sugar-acid ratio, but also to morphological characteristics, e.g., firmness [22] [23], and physiological disorders at ripening stage, e.g., Fuji stain, lenticel marking [24], bitter pit [25], and watercore [26]. During the development of the epidermal tissue, unfavorable climatic conditions can cause stress leading to hysteresis of specific metabolic systems resulting in peel dysfunction or aberrations [27].…”
Section: Summer Seasonmentioning
confidence: 99%
“…Along with chilling hours, change in temperature also leads to stunted growth, diseases and ultimately the quality of the apple crop. A study on different regions of China has made it clear that change in temperature leads to the deterioration of the quality of apple crop [40] and following the law of nature similar conditions leads to low quality / low production of apple in Himachal Pradesh. The impact of changing temperature has also been noted by Kumar et al (2009) in the productivity of cabbage seeds in north western Himalaya [41].…”
Section: Plos Onementioning
confidence: 99%